USE OF CURVED SCANLINES AND BOREHOLES TO PREDICT FRACTURE FREQUENCIES - Peacock D.C.P.; Harris S.D.; Mauldon M. (My University, 2003)
We advance the method of Hudson and Priest (Journal of Rock Mechanics and Mining Sciences & Geomechanics Abstracts 20 (1983) 73-89) to develop a method for a curved scanline to be used to predict the numbers of fractures that would be observed in any direction. When sampling along a scanline, the probability of intersecting a fracture is influenced by the relative orientations of the fracture and of the scanline at that location. This sampling bias can be minimised by the use of the Terzaghi correction, w=(cosχ)-1, where χ is the angle between the scanline and the normal to the fracture. These corrected frequencies are used to simulate fracture frequencies for all other orientations by doubly-correcting the data. Modelled fracture frequency is contoured on a graph of simulated scanline plunge against simulated scanline azimuth. This method is based upon the assumption that the data collected along the scanline is representative of the fracture population when the Terzaghi correction has been applied.A graph of cumulative frequency of fractures against distance along a scanline provides a simple method for determining whether the scanline crosses differently fractured areas. Frequencies are corrected for dip, strike, and both dip and strike, with data from homogeneously fractured areas plotting as straight lines. These frequencies can be normalised for ease of comparison.
Keywords: FRACTURE DATA; DENSITIES; SCANLINES; MEASUREMENTS; FREQUENCY